Evaluation of antibiotic resistance of Helicobacter pylori bacteria obtained from gastric biopsy samples: A cohort study. (June 2022) - Azadbakht, Saleh; Moayyedkazemi, Alireza; Azadbakht, Salehe; Fard, Siamak Alihoseini; Soroush, Setareh
Abstract: Objective: Helicobacter pylori infection is associated with a wide range of gastrointestinal diseases and is very common in developing countries. Overuse and self-prescribed antibiotics have led to antibiotic resistance and failure of complete eradication of the bacterium. The aim of this study is to evaluate the antibiotic resistance of h. pylori from samples obtained from gastric biopsy. Methods: In this descriptive-analytical study was performed on 205 patients' samples positive for h. pylori infection. Following h. pylori testing, the sample were culture with different antibiotics to obtain data regarding the resistance. Demographic information of the patients such as age, sex, employment status, area of residence and patient-related factors such as reason for referral, and previous history of treatment were obtained and evaluated for the correlation with antibiotic resistance. Results: In this study, the mean age of the subjects was 42.32 ± 16.65 years. The most common reason for referral of patients in the present study was epigastric pain in 49.3% (101 patients). Antibiotic resistance to amoxicillin was 46.8%, tetracycline was 41%, metronidazole was 33.2%, clarithromycin was 70.7%. levofloxacin was 36.1% and bismuth was 19.5%. Sex, age, type of living (rural or urban), employment, reason for referral and history of treatment was not associated with any antibiotic resistance, p > 0.05. Conclusion: Our study showed that clarithromycin resistance is the most common in our population followed by amoxicillin and tetracycline. Excessive use of these antibiotics and self-prescription should be analyzed in future studies and public-awareness programs might be required. Highlights: H.pylori infection is associated with a wide range of gastrointestinal diseases. Self-prescribed antibiotics have led to antibiotic resistance and failure of complete eradication. Clarithromycin resistance is the most common in our population followed by amoxicillin and tetracycline.